FACTORS AFFECTING THE COMMUNICATION SKILLS AMONGST THE UNDERGRADUATE MEDICAL IMAGING STUDENTS AT THE INTERNATIONAL ISLAMIC UNIVERSITY MALAYSIA (IIUM) KUANTAN, PAHANG - MOHD NOOR, NUR EMELIYA NATASHA; MOEY, SOO FOON (International Journal of Allied Health Sciences, 2022)
Background: Communication skills are skills that students should equip themselves for the job market and creating positive effects on patients leading to better patient care. As such, this study was conducted to ascertain the communication skills and factors that affect the communication skills amongst undergraduates Medical Imaging IIUM Kuantan. Methodology: One hundred undergraduate Medical Imaging students from the first year to the fourth year at IIUM Kuantan were randomly selected as respondents for the study. Data was collected using a self-developed questionnaire that had undergone content and reliability validation. Results: The results revealed that the communication skills level amongst respondents was high. The Kruskal Wallis test indicated insignificant differences between years of study of the respondents and communication skills level (p>0.05). The Chi-Square test indicated anxiety, lack of confidence, speech impairment, poor language command and lack of practice are the associated factors that affect communication skills amongst the respondents. Discussion: The respondents’ communication skills were influenced by anxiety and confidence especially during job interview which then affect their ability to communicate effectively and assertively. Poor language command was also found to influence the individual to be an effective communicator. Additionally, lack of practice in communication skills can introduce conflicts due to usage of inappropriate conversation in different situations. Conclusion: University students should continuously improve their communication skills to prepare them for the job market.